Hypertriglyceridemic waist phenotype: Association with initial neurological severity and etiologic subtypes in patients with acute ischemic stroke - Ren, Yuan; Qiu, Zi-Han; Wu, Wei-Hua; Dong, Xiao-Guang; Han, Shuang; Zhang, Fu-Liang; Kong, Fan-Li; Li, Feng-E (Frontiers in Endocrinology, 2022)
Objective: To explore the relationship of hypertriglyceridemic-waist phenotype (HTWP) with initial neurological severity and etiologic subtypes in patients with acute ischemic stroke. Methods: Data for this study were collected from hospitalized patients within 72 h of acute ischemic stroke onset of department of neurology at the Affiliated Hospital of Beihua University from July 1, 2020, to June 30, 2022. The extent of initial neurological severity was assessed by the National Institute of Health Stroke Scale (NIHSS) on the day of admission, NIHSS<6 was defined as mild stroke and NIHSS≥6 was defined as moderate to severe stroke. HTWP was defined by fasting serum triglycerides≥1.7mmol/L and waist circumference ≥90 cm in male, ≥80 cm in female. Differentiation of etiologic subtypes were based on the method reported in the Trial of Org 10 172 in Acute Stroke Treatment (TOAST).Multivariate logistic regression analysis was used to analyse the association of HTWP with initial neurological severity and etiologic subtypes. Results: A total of 431 patients were included. Compared with the NWNT group, patients with HTWP had reduced risks of moderate to severe stroke (OR 0.384, 95%CI 0.170-0.869; P=0.022). In additon, the risk of small-artery occlusion stroke was 2.318 times higher in the HTWP group than in the normal triglyceride-normal waist group (OR 2.318, 95%CI 1.244-4.319; P=0.008). Conclusion: Initial neurological severity was less severe in patients with HTWP, and HTWP was associated with an increased risk of small-artery occlusion stroke.